Middle interhemispheric variant of holoprosencephaly: First prenatal report of a ZIC2 missense mutation - Gounongbé, Caroline (Clin Case Rep, 2020)
We present a case of a middle interhemispheric variant of antenatal discovery associated with a de novo missense variant (NM_007129.5: c.1109G>A p.(Cys370Tyr)) in the ZIC2 gene. Our case represents the first prenatal description of a ZIC2 missense mutation found in association with syntelencephaly.